Central Cambridge a guide to the university and colleges - Taylor, Kevin 1961- (Cambridge University Press, 2008)
The fully revised and updated second edition of this best-selling guidebook is intended for all visitors to Cambridge, and for anyone with an interest in the University. Combining an accessible style with accuracy of fact and a wealth of historical detail, it can be used to accompany a walking tour or read at leisure as an authoritative introduction. The second edition is packed with newly commissioned colour photographs by Japanese artist and photographer Hiroshi Shimura, as well as fresh maps and added information about the buildings and developments of recent years. Central attractions receive full entries, and the book also offers historical descriptions of all the outer-lying colleges, making it a comprehensive survey of the collegiate University. There is an informative introduction, a list of colleges with foundation dates, a substantial glossary and index, and a list of further reading material, all extended and updated for this edition
Keywords: University of Cambridge / Guidebooks; University of Cambridge; Führer